ANALISA DAYA SAING PABRIK GULA-PABRIK GULA MILIK BUMN - ALMAMALIK, LUKMANULHAKIM (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2017)
This study aimed to identify issues related to competitiveness in state-owned sugar mills. The balanced scorecard approach and Porter's competitiveness model are used to analyze and evaluate the competitiveness of the state-owned sugar mills. The data used in this research is taken from survey data in seven state-owned sugar mills in Java. The results show that the state-owned sugar mills that have very good competitiveness categories are only one factory, 2 sufficient factories, and less than 2 factories. From the results of this study can later be used as a reference in rearranging the state-owned sugar mills industry in order to improve the competitiveness of the national sugar industry.